Determining melt productivity of mantle sources from U-238-Th-230 and U-235-Pa-231 disequilibria; an example from Pico Island, Azores - Prytulak, J; Elliott, T (2009)
We use coupled 238U-230Th and 235U-231Pa disequilibria measurements from Pico Island, Azores to examine the melting behavior of the underlying mantle. U-series disequilibria in young, mafic lavas are dependent on the melting rate of their source, which in most cases is primarily controlled by its melt productivity. Mafic lithologies such as eclogite and pyroxenite have much higher melt productivities than peridotite and so U-series measurements may provide constraints on the mineralogy of the melting mantle. Recent Pico Mountain lavas show limited geochemical variations and a restricted range of U-series disequilibria with (230Th/238U) = 1.22-1.25 and (231Pa/235U) = 1.46-1.50. Using a simple, dynamic melting model of a homogeneous source, these results can be reproduced with melting rates of <1 × 10-4 kg/m3/a and melt porosities of <0.7% near the onset of melting. For a plausible range of upwelling rates, this implies that the melt productivity is <6%/GPa. This value is consistent with a garnet peridotite source but not with more highly productive mafic lithologies. Given independent evidence for the involvement of mafic lithologies such as recycled oceanic crust in Pico magmagenesis, we suggest a scenario in which initial eclogitic melts are dispersed through melt-rock reaction into a larger volume of surrounding peridotite. Subsequent re-melting of the resultant incompatible element enriched peridotite carries a geochemical signature of the mafic lithologies but not necessarily a record of their high melt productivity. © 2009 Elsevier Ltd. All rights reserved.